“Our needs, our priorities, listen to us!” recommendations for improving HIV prevention and the cascade of care from people living with HIV in Manitoba, Canada: a qualitative study - Enrique Villacis-Alvarez; Margaret Haworth-Brockman; Katharina Maier; Cheryl Sobie; Heather Pashe; Joel Baliddawa; Nikki Daniels; Rebecca Murdock; Robert Russell; Clara Dan; Freda Woodhouse; Susie Cusson; et al. (BMC Health Services Research)
Abstract Background The Canadian province of Manitoba has reported a 52% increase in HIV diagnoses during the past 5 years. Females are disproportionately affected by HIV and multiple intersecting health and social challenges, including houselessness, injection drug use, sexually transmitted and blood borne infections, and mental health conditions. Program and service development often ignore people’s complex lived experiences. Our aim was to describe recommendations made by people living with HIV (PLHIV) to inform a person-centred HIV cascade of care valuing the needs and ideas from PLHIV. Methods This qualitative study was conducted between October 2022 and May 2023. Thirty-two women, men, and gender-diverse participants completed a semi-structured interview. Interviews were recorded, transcribed, and analyzed using NVivo 12, deploying thematic analysis to understand major themes related to recommendations to care. This manuscript focuses on questions related to recommendations for the HIV cascade of care. Results Recommendations fell within two major themes: ‘Meeting people where they are at’ and an HIV educational strategy. The first theme included three main categories to make HIV services more accessible. (1) psychological (social programming, peer support during diagnosis, increased mental health services), (2) biomedical (HIV outreach, HIV services outside 9 –5 h, specialized care outside metropolitan areas, universal coverage for HIV medicines), and (3) social (transportation support, emergency housing, financial support) supports. The HIV educational strategy included five major categories: (1) physical posters and billboards in highly transited areas; (2) community meetings with peer-led education; (3) comprehensive sex education in schools; (4) training primary healthcare providers on stigma and discrimination; (5) and social media campaigns to reach younger audiences. We report on gender differences for recommendations where they arose. The themes described by PLHIV suggest a need to implement HIV care delivery models that will connect and maintain people in HIV care in Manitoba. Conclusions This study provides practical and person-centred strategies that could bridge the barriers PLHIV face when accessing and remaining in HIV care and expanding education and prevention about HIV in Manitoba.